Trends in Prevalence, Treatment, and Relationship of Metabolic Syndrome and Individual Components by Race/Ethnicity, 1999-2018 - Yuan Lu, ScD; Xumin Li, MS; Yuntian Liu, MPH; César Caraballo, MD; Daisy Massey, BA; Shiwani Mahajan, MD, MHS; Erica Spatz, MD, MHS; Jeph Herrin, PhD; Harlan M. Krumholz, MD, SM (JACC: Advances)
Background: Nationally representative data on recent trends in racial/ethnic differences in metabolic syndrome (MetS) prevalence and treatment are sparse. Objectives: The purpose of this study was to examine 20-year trends in the prevalence, treatment, and interrelationships of MetS and its individual components among U.S. adults, overall and by race/ethnicity. Methods: We evaluated trends from 1999 to 2018 in 20,397 adults using data from the National Health and Nutrition Examination Survey. Age-standardized prevalence estimates were calculated for MetS, its components, and related prescription drug use. Trends were assessed using weighted linear regression, and racial/ethnic disparities were examined using t-tests. Results: The mean age was 47.5 (47.4-47.6) years; 51.3% were female; 77.9%, 12.8%, and 9.4% were White, Black, and Hispanic, respectively. MetS prevalence increased significantly from 1999 to 2018 across all groups (P < 0.001). Among MetS components, waist circumference and fasting glucose increased across all groups, while triglycerides increased only among Black individuals. Lipid-lowering medication use increased (P < 0.001), but racial/ethnic disparities persisted. Compared to White individuals, Hispanic individuals had lower antihypertensive and lipid-lowering medication use (P < 0.01). Despite increased prescriptions, <65% of eligible individuals received lipid-lowering therapy, and <35% received antihyperglycemic therapy, highlighting substantial treatment gaps. Racial/ethnic differences in MetS component relationships were observed: blood pressure played a larger role in Black individuals, while fasting glucose was more prominent in Hispanic individuals. Conclusions: MetS prevalence has increased over 2 decades. Persistent racial/ethnic disparities exist in antihypertensive, antihyperglycemic, and lipid-lowering medication use. Across all racial/ethnic subgroups, large opportunities remain for improving treatment strategies among individuals with medication indications.